Understanding Farm Diversity through Typology for Technological Interventions in Western Plain Zone of Uttar Pradesh, India - Raghavendra, K.J.; Meena, L.R.; Meena, A.L.; Dutta, Debashis; Nirmal, Nirmal; Kumar, Devendra; Panwar, A.S. (Indian Journal of Extension Education, 2021)
The farming systems having diverse characteristics need to be understand for tailored technological interventions. Farm typology designates the heterogeneous farmers’ characteristics in to homogenous groups to understand the factual situation in the region. The multivariate analysis viz. PCA and Cluster analysis performed to minimize data and group them into homogenous characteristics by various farm variables. A cross section survey of 120 farmers in WPZ of Uttar Pradesh was carried out and identified 9 significant variables and generated 4 PCs from PCA. Hierarchical clustering of PCs leads to grouping farms into homogenous class. The predominant farm types based are type-1 (22.5%) livestock based intensive farms, type-2 (23.3%) are resource endowed large farms, type-3 (10.8%) are crop based marginal farms and type-4 (43.3%) are small farmers with high profit margin. Large farms are integrated with crop and animal components earning higher income. The results show that the diversified farms with both livestock and crop sectors are reaping better income and technology adoption capacities.